(untitled) (Research, Society and Development, 2021)
Objective: To synthesize the findings of chronic effects and the differences between the volume of repetitions and levels of external loads in the pressure responses of elderly hypertensive patients. Methods: The study followed the proposals of PRISMA (Preferred Reporting Items are Systematic Reviews and Metanalysis). As searches for the selected articles on the Medline, Pub Med, Cochrane, and Periodical platforms, between August and December 2020. The same studies were found using several words according to the proposed theme. ("Resistance training" and "elderly") ("Resistance training" and "blood pressure") ("Resistance training" and "cardiovascular and elderly") ("Resistance training" and "blood pressure" and "elderly") ("Resistance training" and "blood pressure" and "older"). Results: 2,698 articles were identified with these keywords. Title, abstract, duplicates excluded studies and after reading in full. Finally, ten studies were selected to read the integration, and four were selected for final analysis. Conclusion: This systematic review study uses low repetition and repetition to reduce similar magnitudes’ blood pressure. The levels of external loads did not interfere in large proportions in hypertensive older adults’ pressure responses. However, studies on the post-exercise resistance hypotensive effect and its variables are still scarce, making further studies on the subject necessary.